Novel Flat Data Center Network Architecture Based on Optical Switches With Fast Flow Control - Fulong Yan; Wang Miao; Harm Dorren; Nicola Calabretta (IEEE Photonics Journal, 2016)
We propose a novel flat and scalable data center network (DCN) architecture based on fast (nanosecond) distributed buffer-less optical switches and efficient optical flow control. The proposed DCN architecture scales as the square of the port count of the optical switches. In order to investigate the performance of the proposed architecture, the system operation of an electronic Top-of-the-Rack (ToR) and the optical switch is fully described, and all functional subsystems are modeled. The performance in terms of DCN scalability, average latency, packet loss, normalized throughput of the network, and electronic buffer size of the ToR is numerically assessed for a medium-size data center supporting 5760 servers and a large-size data center connecting 100 000 servers. Considering a traffic pattern with high inter-cluster (40%) traffic distribution and buffer size of 40 KB, the results report an end-to-end latency of less than 8.1 $μ\text{s}$ (including retransmission) and a packet loss $<\ 10^{-7}$ under a load of 0.4 for the large-size data center. Moreover, we provide a preliminary experimental validation of the DCN by using a 4 $×$ 4 optical switch prototype showing dynamic switching at 40 Gb/s and error-free operation with less than 1.5 dB penalty for the longest path.